Colectomy with ileorectal anastomosis has a worse 30‐day outcome when performed for colonic inertia than for a neoplastic indication. (27th March 2013) - Reshef, A.; Gurland, B.; Zutshi, M.; Kiran, R. P.; Hull, T.
Abstract Aim Whether bowel related dysfunction adversely affects postoperative recovery after total colectomy with ileorectal anastomosis (C + IRA) for colonic inertia (CI) has not been previously well evaluated. This study compared the early postoperative outcome of C + IRA for CI and for other noninflammatory indications. Method Patients undergoing elective C + IRA from 1999 to 2010 were identified from a prospectively maintained database. Since inflammation in the rectum or small bowel may influence the outcome, patients with inflammatory bowel disease were excluded. Patients undergoing surgery for CI (group A) were compared with patients having the operation for other benign noninflammatory diseases (group B). Demographics, American Society of Anesthesiologists (ASA) score, body mass index (BMI), surgical procedure and 30‐day complications were assessed. Results The study population consisted of 333 patients undergoing elective C + IRA (99 men, mean age 39 ± 16 years). The procedure was laparoscopic in 163 (49%) patients. Groups A (n = 131) and B (n = 202) had similar age and ASA score (39 ± 11 vs 39 ± 19 years, P = 0.4; 2.2 ± 0.5 vs 2.4 ± 0.7). Group A patients had lower BMI (25 ± 5 vs 28 ± 8 kg/m2, P = 0.002), more women (99 vs 51%, P < 0.001) and fewer laparoscopic procedures (43 vs 53%, P = 0.04). Compared with group B, group A had a greater incidence of postoperative ileus (32 vs 19%, P = 0.009), higher overall morbidity (36 vs 15%, P < 0.001) and increased length of stay (8.4 ± 6 vs 7.2 ± 5 days, P < 0.006). These differences persisted when subgroups of patients who underwent laparoscopic or open surgery were compared. Conclusion Although CI is considered a 'benign' condition, patients undergoing C + IRA for this indication have significant morbidity compared with patients having the operation for other noninflammatory benign conditions.